ACCOUNTABILITY VALUES FOR THE PERFORMANCE IN PRIVATE ISLAMIC UNIVERSITY - Wa Ode Rayyani; Hannani Hannani (Jurnal Al-Dustur, 2020)
The study aims to reveal the values of performance accountability in private Islamic universities. Type of qualitative research was used in this study by reviewing literature in the context of private Islamic universities. The three objects in this study were Universitas Islam Indonesia, Universitas Muslim Indonesia, and Universitas Muhammadiyah Yogyakarta. The result of this study revealed that the private Islamic universities are promoting Islamic values in their performance accountability. The accountability value of a private Islamic university includes trust in work, which consists of professionalism, honest, worship and charity deeds as well as exploring the religion and professions for understanding the value of religious ordinances and diligently working.